Empowering Future Bilingual Educators: Integrating Trauma-Informed Approaches in Bilingual Teacher Education - Razmeh, Shakiba; Salgado, Yolanda (Language, Technology, and Social Media, 2024)
The impact of trauma on children's social, emotional, and academic growth is profound, yet teacher preparation programs, particularly in bilingual and multicultural contexts, often lack comprehensive training in trauma-informed practices. This qualitative study investigates the integration of trauma-informed approaches into a bilingual teacher education course at a university in West Texas. The study included 59 undergraduate pre-service teachers enrolled in a course on bilingual and multicultural education. Data were collected through preliminary and concluding written interviews, alongside ongoing instructional interventions, including discussions, case analyses, and trauma-informed strategies. Initially, participants demonstrated a limited understanding of trauma, associating it primarily with extreme events such as accidents or death. Post-course assessments, however, revealed a broadened understanding, recognizing everyday traumas like poverty, bullying, and family instability. Findings suggest that integrating trauma-informed approaches significantly enhances pre-service teachers' ability to identify and apply practical strategies to support trauma-affected students. The study introduces the Trauma-Informed Bilingual Teacher Preparation Model, focusing on key components such as foundational trauma knowledge, recognizing trauma symptoms, culturally responsive teaching, creating supportive environments, and fostering teacher resilience. By embedding trauma-informed practices in teacher education, this model prepares future educators to cultivate compassionate, inclusive classrooms, particularly in bilingual and multicultural settings. The study emphasizes the importance of curriculum reform to equip teachers with the necessary skills to support both students' emotional well-being and academic success.